Correlation between the Quality of Public Services and the Image of Institution to the Public Satisfaction at Kejaksaan Negeri Jember - Danang Hadi Wijoyo (ABM: International Journal of Administration, Business and Management, 2024)
The quality of public services and the image of the institution are considered as crucial things for the government institution. With that in mind, this research is intended to analyze the correlation between those things and public satisfaction, in this case, at Kejaksaan Negeri Jember. Quantitative descriptive was implemented to cope with the previous research objectives. One hundred and two respondents were selected using a nonprobability sampling technique with a quota sampling. The data gathered from those respondents were analyzed using a Structural Equation Model (SEM) approach based on Partial Least Square (PLS) with two evaluation stages which cover: 1) the measurement model and 2) the structural model. Based on the measurement model, the results passed the convergent validity test, discriminant validity test, reliability test, and multicollinearity test. In line with this, the structural model shows that based on the significance test there is a correlation between the quality of public services and the image of the prosecutor's office on public satisfaction at Kejaksaan Negeri Jember. It is expected that in the future, Kejaksaan Negeri Jember will continue to maintain and increase the current condition to provide more comprehensive benefits to the society